THE IMPLICATION OF ABU TEUPIN RAYA’S THOUGHT IN TRANSFORMING ISLAMIC EDUCATION IN ACEH - Al Husaini M Daud (Journal of Contemporary Islam and Muslim Societies, 2021)
Abstract: This research is a study of the history of an educational figure about the implication of Islamic education related to the thoughts of Abu Teupin Raya, one of prominent educational figure from Aceh. Historical and sociological approach of knowledge were used. Meanwhile, the primary sources were the textual works of Abu Teupin Raya. Another major source was informants, those were the children of figure who were still alive and his students who had learned directly from him. Methods of data collection were done through the study of any literatures and in-depth interviews. All data collected was then selected, classified, verified systematically to the problem and the scope of the study. Furthermore, the data was analyzed by using content analysis and historical continuity method. This study found; First, the process of transformation of Islamic education in Aceh was closely linked with the historical, philosophical, and sociological foundation. Second, the idea of Islamic education which were transformed in the form of Islamic boarding institutions in Aceh had positive implications not only to the paradigm changes in the system of Islamic education but also to the management of educational institutions, financial administration system, even the curriculum and teaching methods.Keywords: Abu Teupin Raya, transforming, Islamic education, Aceh